High strength mortars using ordinary Portland cement-fly ash-fluid catalytic cracking catalyst residue ternary system (OPC/FA/FCC) - Soriano, L.; Payá, J.; Monzó, J.; Borrachero, M. V.; Tashima, M. M. [UNESP] (Elsevier, 2016)
The use of ternary systems composed of ordinary Portland cement (OPC) and two pozzolanic mineral admixtures could supply several advantages in terms of the properties in both fresh and hardened states. Fly ash (FA) and spent fluid catalytic cracking catalyst (FCC) were combined to produce high strength mortars due to a synergic effect. OPC/FA systems (70%/30%) and OPC/FA/FCC systems (70%/20%/10%) were analyzed by thermogravimetric and SEM techniques. Mortars with different binder/sand ratios were prepared in order to yield high compressive strength values. On the one hand, fly ash particles act as nucleation sites that favour the hydration of Portland cement particles: at early stages (7 days), the calculated fixed hydrated lime values were negative, suggestive of a nucleating effect. For a longer curing period (90 days), the pozzolanic effect develops, as can be noted in terms of its compressive strength behaviour. The 90-days curing strength for OPC/FA mortars ranged between 96 and 98 MPa. In ternary mixtures (OPC/FA/FCC), FCC act as pozzolan during the initial 7 days period; the presence of fly ash particles favoured the presence of more portlandite by means of the nucleation effect. For longer curing times, fly ash particles also contribute to strength development, producing a synergic effect with FCC. The 90 days curing strength for OPC/FA/FCC mortars ranged between 103 and 106 MPa. Binary and ternary mortars reached strength activity index values equal or higher to the unit. Contributions to the strength (i.e. hydration of cement, the nucleation effect, and early and long term pozzolanic effects) have been calculated for 7 and 90 curing days pozzolan-containing mortars.
Keywords: FCC; Fixed hydrated lime; Fly ash; High strength mortar; Pozzolan